Moral Emotion and Moral Identity on Moral Judgement Maturity Among Malaysian Secondary School Students - Appalanaidu, Sathish Rao; Balakrishnan, Vishalache; Yan-Li, Siaw (Universitas Pendidikan Ganesha, 2024)
In preparation for the challenges of the real world and life after school, moral judgement stands as a pivotal skill among Malaysian secondary school students. Understanding the moral motivating factors contributing to the development of moral judgement maturity is imperative. Therefore, this study aims to analyze the relationships between moral motivation components—specifically, moral emotion (guilt and shame) and moral identity—and moral judgement among Malaysian secondary school students. A sample of 393 students (170 males, 223 females; M age = 16 years) from Selangor state participated in the study. Structural equation modelling (SEM) was utilised to analyse the predictive associations between these constructs. The findings revealed positive correlations among moral emotion, moral identity, and moral judgement. Notably, both guilt and shame, as well as moral identity, were found to be significantly related to students' moral judgement maturity. These results suggest that the tendency for experiencing guilt and shame, along with a heightened moral identity, play pivotal roles in shaping the moral judgement maturity of secondary school students, potentially fostering their moral development. This study contributes valuable insights into the mechanisms linking emotions and identity to moral judgement maturity, offering significant implications for the field of moral psychology.